Role of STAT3 in the pathogenesis of nasopharyngeal carcinoma and its significance in anticancer therapy - Si, Yishimei; Xu, Jinjing; Meng, Linghan; Wu, Yuanqing; Qi, Jianwei (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is a type of head and neck tumor with noticeable regional and ethnic differences. It is associated with Epstein-Barr virus infection and has a tendency for local and distant metastasis. NPC is also highly sensitive to radiotherapy and chemotherapy. Over 70% of patients present with locoregionally advanced disease, and distant metastasis is the primary reason for treatment failure. A signal transducer and activator of transcription 3 (STAT3) promotes NPC oncogenesis through mechanisms within cancerous cells and their interactions with the tumor microenvironment, which is critical in the initiation, progression, and metastasis of NPC. Further, p-STAT3 is strongly associated with advanced NPC. Recent research on STAT3 has focused on its expression at the center of various oncogenic pathways. Here, we discuss the role of STAT3 in NPC and its potential therapeutic inhibitors and analogs for the treatment and control of NPC.